Adat Basandi Syarak sebagai Modal Sosial Keagamaan dalam Membangun Jaringan Kekerabatan pada Pedagang Minang di Medan - Wulan Zani Tanjung; Faisal Riza; Aulia Kamal (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
This study examines the role of the Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK) philosophy in shaping religious social capital and kinship networks among Minangkabau traders in the multi-ethnic and multi-religious city of Medan. The background of this research is rooted in the ability of Minangkabau traders to maintain their traditional and religious identities within modern economic activities. This study aims to analyze how the ABS-SBK philosophy influences business ethics and the patterns of kinship networks in Minangkabau trading practices in Medan. This research employs a qualitative method with a descriptive approach, utilizing observation, in-depth interviews, and documentation techniques. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing, supported by source triangulation. The findings indicate that ABS-SBK functions as a moral guideline and a form of religious social capital that fosters trust, solidarity, and perceived business blessings. Kinship networks are formed through blood relations, shared regional origins, and customary-religious commitments, which are practiced through principles of mutual assistance, cooperation, and trust. In conclusion, the ABS-SBK philosophy serves not only as a cultural and religious identity but also as a relevant economic strategy and a model of local wisdom-based business ethics in the modern era.